2014
DOI: 10.1038/nsmb.2819
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for protein-RNA recognition in telomerase

Abstract: Telomerase is a large ribonucleoprotein complex minimally composed of a catalytic telomerase reverse transcriptase (TERT) and an RNA component (TR) that provides the template for telomeric DNA synthesis. However, it remains unclear how TERT and TR assemble into a functional telomerase. Here we report the crystal structure of the conserved regions 4 and 5 (CR4/5) of TR in complex with the TR-binding domain (TRBD) of TERT from the teleost fish Oryzias latipes. The structure shows that CR4/5 adopts an L-shaped th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
145
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(153 citation statements)
references
References 38 publications
4
145
0
Order By: Relevance
“…3A and B) (18,19). Within the CR4/5 domain, the loop and base of helix P6.1 have been shown to be especially important (40)(41)(42). Using our circular-permutation analysis, we found that disrupting the backbone between CR4/5 and the core is tolerated to different degrees.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…3A and B) (18,19). Within the CR4/5 domain, the loop and base of helix P6.1 have been shown to be especially important (40)(41)(42). Using our circular-permutation analysis, we found that disrupting the backbone between CR4/5 and the core is tolerated to different degrees.…”
Section: Resultsmentioning
confidence: 97%
“…These mutations could affect the essential CR4/5 TERT-binding function (18) or RNA conformational changes. For instance, the medaka fish CR4/5 binds to the RNA-binding domain of TERT and undergoes a dramatic rearrangement of the three-way junction compared to unbound RNA (40). In contrast, circular permutations at the 5= and 3= borders of CR4/5 (CP242 and CP328) show strong or detectable activity (Fig.…”
Section: (6)mentioning
confidence: 99%
“…The telomerase activation domain consists of the stem loops P6a/b, P6.1, and P5 (15) and is coordinated by the VSR motif of TRBD and motifs E-II and E-III (FVYL pocket) of the thumb domain (6,9,10). Although CR4/5 is primarily coordinated by the TRBD, its stem loop P6.1 extends across the TRBD-thumb interface and binds the FVYL pocket of the thumb domain (6).…”
mentioning
confidence: 99%
“…1B) (33). A solution NMR structure of the medaka TR (mdTR) activating domain (CR4/5) and the crystal structure of the CR4/5-TRBD complex have been reported (34,35). These structures show that phylogenetically conserved bases interact with the TRBD, suggesting that the mode of interaction is conserved among vertebrates (34).…”
Section: Significancementioning
confidence: 99%
“…A solution NMR structure of the medaka TR (mdTR) activating domain (CR4/5) and the crystal structure of the CR4/5-TRBD complex have been reported (34,35). These structures show that phylogenetically conserved bases interact with the TRBD, suggesting that the mode of interaction is conserved among vertebrates (34). Based on sequence comparisons, the medaka t/PK domain is predicted to have the minimal pseudoknot and P2ab, but not P2a.1, and its J2a/3 loop is much longer than in hTR (Fig.…”
Section: Significancementioning
confidence: 99%